2018
DOI: 10.1080/2162402x.2018.1474318
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose cyclophosphamide depletes circulating naïve and activated regulatory T cells in malignant pleural mesothelioma patients synergistically treated with dendritic cell-based immunotherapy

Abstract: Rationale: Regulatory T cells (Treg) play a pivotal role in the immunosuppressive tumor micro-environment in cancer, including mesothelioma. Recently, the combination of autologous tumor lysate-pulsed dendritic cells (DC) and metronomic cyclophosphamide (mCTX) was reported as a feasible and well-tolerated treatment in malignant pleural mesothelioma patients and further as a method to reduce circulating Tregs.Objectives: The aim of this study was to establish the immunological effects of mCTX alone and in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…By contrast, Noordam et al found no correlation between the overall Treg level and survival. However, in this study, when the authors distinguished naive from effector Treg cells, they observed that the nTreg level corresponded with improved survival [17]. Noordam et al [17] have demonstrated that the number of naïve Treg (nTreg) cells in the peripheral blood positively correlates with survival in malignant pleural mesothelioma patients.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…By contrast, Noordam et al found no correlation between the overall Treg level and survival. However, in this study, when the authors distinguished naive from effector Treg cells, they observed that the nTreg level corresponded with improved survival [17]. Noordam et al [17] have demonstrated that the number of naïve Treg (nTreg) cells in the peripheral blood positively correlates with survival in malignant pleural mesothelioma patients.…”
Section: Introductionmentioning
confidence: 70%
“…Noordam et al analyzed the overall Treg cell levels in the peripheral blood as these were shown to correlate with decreased survival in malignant pleural mesothelioma patients. However, when they divided the Treg population into naïve and effector cells, they observed that nTreg levels corresponded with improved survival rates [17]. Notably, Chung demonstrated that CD4+ T cell infiltration in patients with breast cancer is linked with improved survival rates, but breast cancer patients with a high percentage of FoxP3+/CD8+ within the CD4 + Tcells have decreased survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, depletion of Tregs was not correlated with a better clinical outcome. However, detailed analysis of naive Tregs (nTregs, CD45RA + FoxP3 int ) and activated Tregs (aTregs, CD45RA − FoxP3 hi ) showed a positive correlation between the pretreatment levels of nTregs and OS 128 . In addition, results from this clinical study are quite promising, with patients still alive up to 6 years after diagnosis.…”
Section: Main Textmentioning
confidence: 67%
“…Grade III/IV toxicities did not occur. Moreover, cyclophosphamide treatment indeed selectively depleted Tregs and the frequency of naïve Tregs prior to treatment was positively correlated to OS (61). Two patients were still alive 6 years after diagnosis.…”
Section: Tumor Lysate Loaded Dc-therapymentioning
confidence: 90%